Implementation And Impact Of E-Health Care (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Health sector is a growing field and health conscience has been a  major concern for everyone. Particularly in the health care sector,  Information and communication Technology, enabled devices like  Smart phones, Tablet PC, Sensors etc are predominantly used for  ease of access and use towards decision processing. Application of intelligent agent technology in health care sector  pertaining to hospital search & appointment, patient health  monitoring and mobile health record can be done by the help of  e-health care. Health Information can be used on Online Social Networks provide  a novel opportunity to improve public health through effective  health information dissemination. Implementation of an integrated system for the delivery of health  related services, based on different technologies and devices that  allow collecting and displaying data from biomedical sensors, to  manage user’s reminders for medicines, and to monitor the patient’s  dietary habits. Implementation proves the feasibility of the proposed  service, and the possibility to gain users’ adherence and compliance,  through proper design criteria. The present paper discusses the challenges and opportunities in ICT  implementation in health care.
Keywords: ICT; eHealth; healthcare providers